Prospective randomized comparison of the transobturator mid-urethral sling with the single-incision sling among women with stress urinary incontinence: 1-year follow-up study - Jurakova, Michaela; Huser, Martin; Belkov, Ivan; Janku, Petr; Hudecek, Robert; Stourac, Petr; Jarkovsky, Jiri; Ventruba, Pavel (International urogynecology journal, 2016)
INTRODUCTION AND HYPOTHESIS: The objective was to compare the efficacy and safety of an innovative single-incision sling (SIS) with the inside-out transobturator sling (TOT) in the treatment of female stress urinary incontinence (SUI). METHODS: A prospective randomized trial was performed in a tertiary referral urogynecology center from January 2012 to December 2013. The study included women with pure urodynamic SUI. Patients were randomized to either the SIS or the TOT anti-incontinence procedure. Surgery duration, blood loss, and groin pain scores were recorded for each patient. The 1-year follow-up visit included objective and subjective cure parameters, postoperative de novo urgency, complications, and the impact on the patient's life quality. RESULTS: Of 285 patients assessed for eligibility, a total of 93 patients (32.6 %) were randomized into TOT (n = 48) and SIS groups (n = 45). There were no significant differences in either operating time or blood loss. A statistically significant difference between the two groups was found in pain scores three (5.6 ± 1.8 vs 3.1 ± 2.1, p < 0.001) and 12 h postoperatively (3.8 ± 1.7 vs 2.1 ± 1.7, p < 0.001). After 1 year, there were no significant differences between the TOT and SIS groups in objective cure rates (87.0 % vs 90.9 %; p = 0.399) or patient-reported success rates (91.3 % vs 93.2 %; p = 0.999). Incidence of postoperative de novo urgency did not differ between TOT and SIS patients. Both groups registered a significant improvement in quality of life. CONCLUSIONS: The Ophira SIS procedure has 1-year success rates comparable to standard TOT with significantly less groin pain in the early postoperative period. Both methods were safe and effective in terms of postoperative urgency and life quality improvement.
Keywords: Urinary Incontinence, Urge; senioři; pooperační bolest; Blood Loss, Surgical; třísla; délka operace; Groin; Suburethral Slings; suburetrální pásky; Efficacy; výsledek terapie; Middle Aged; Stress urinary incontinence; urgentní inkontinence; Single-incision sling; Prospective Studies; Patient Reported Outcome Measures; kvalita života; Follow-Up Studies; Mid-urethral sling; následné studie; krvácení při operaci; ženské pohlaví; Urologic Surgical Procedures; stresová inkontinence moči; Humans; prospektivní studie; hodnocení výsledků péče pacientem; Pain, Postoperative; lidé středního věku; urologické chirurgické výkony; Operative Time; Randomized controlled trial; Urinary Incontinence, Stress; Patient-reported outcomes; Female; Aged; Quality of Life; Treatment Outcome; lidé